Eugenia Jambolana Seed Decrease Blood Glucose Level - I Ketut Sudiana; Tintin Sukartini; Hepta Nur Anugrahini (Universitas Airlangga, 2008)
Introduction: The incidence of diabetes mellitus still increasing and needed a cost-effective complementary therapies such as Eugenia jambolana seeds. Eugenia jambolana seeds contain of Chromium and Tannin. It has been reported that Eugenia jambolana seeds has ability to decrease blood glucose, and increase HDL level significantly. The objective of this study was to investigate the effect of Eugenia jambolana seed to exchange of blood glucose in streptozotocin-diabetic rats. Method: A true experimental post test only control group design was used in this study. A number of 15 male albino Wistar rats weighing 100-200 gram were divided into 3 group (normal group, diabetic group and experiment group), 5 rats in each group. Normal group and diabetic group were given aqua 2ml/200 g bw as placebo. Eksperiment group were fed Eugenia jambolana seeds extract 500 mg/Kg b.w for 15 days. Data were analyzed by using One Way ANOVA with significance level α≤0.05.Result: The result showed that blood glucose level of experiment group was significantly different from diabetic group (p=0,001). Discussion: It can be concluded that Eugenia jambolana seeds extract (500 mg/Kg b.w) has an effect to decrease blood glucose level in streptozotocin-induced diabetic rats.